ANALISIS LINE BALANCING DENGAN METODE MOODIE YOUNGPADAPT. SUKORINTEX BATANG JAWA TENGAH - Irwan Sukendar; Andre Sugiyono; Andy Kurniawan (Jurnal Ilmiah Dinamika Teknik, 2019)
SUKORINTEX is a company that works in the textile industry, which is a production company for woven sarongs. The production system used is MTO (make to order), PT. SUKORINTEX has 5 work stations in the production process, namely preparation, weaving, gray room, finishing and pakaging work stations. Based on the initial observations that were made, there were obstacles where there were several unemployed work stations, while several other work stations were still working in full and there were bottlenecks. Therefore, a balance of trails is needed in order to minimize idle time at each work station.In the initial condition the company is aware of a balance delay value of 57%, line efficiency 43%, smoothness index 1326.95 and the number of work elements 19 and work stations 5. This research was conducted aimed at correcting the imbalance problems that exist within the company using the method line balancing which is the moodie young method. With the application of the moodie young method, improvements were obtained with 28% balance delay, 72% line efficiency, 659.36 smoothness index and 19 work elements and work stations 3. Thus the moodie young method can be used to improve production lines at PT. SUKORINTEX